Expectations of Potential Users Regarding a Pakistani Diet Analysis Software - Minhas , Sana (Nurture, 2009)
The purpose of this study was to identify the need for a food analysis software that will aid the professionals in their work. The study also aimed to assess the needs, and expectations of the people (dieticians, researchers, teachers and students) regarding the food analysis software. The study was conducted in Karachi. The subjects were Dieticians, Researchers, Teachers and Students. The data was collected through interviews conducted with the help of a questionnaire. The results showed that a very small percentage of respondents use software for Diet Analysis but all the respondents (100%) considered the need of Pakistani Diet Analysis Software. The respondents wanted it to be user friendly and preferred the software to work using both food composition tables (FCT) and food exchange list. They prefer to see comprehensive results that include values for calories, fuel nutrients, vitamins and minerals. It can be concluded from the responses that Pakistani Diet Analysis Software is a much needed tool for the Dieticians, Students, Teachers and Researchers.